Supplemental data: Hotspots of diffusive CO₂ and CH₄ emission from tropical reservoirs shift through time - Paranaíba, José Reinaldo; Barros, Nathan; Almeida, Rafael M.; Mendonça, Raquel; Linkhorst, Annika; do Vale, Roseilson; Roland, Fábio; Sobek, Sebastian (Uppsala University, 2020)
Ten sampling campaigns were performed in four tropical reservoirs in Brazil between 2015 and 2017. The reservoirs are located in three different biomes, and are different in size, age, type of flooded soil, trophic state, and type of use.

We performed spatially resolved measurements of dissolved CO2 and CH4 surface water concentrations and their gas-exchange coefficients (k) to compute diffusive carbon flux from four contrasting tropical reservoirs across Brazil during different hydrological seasons. We used an online equilibration system to measure dissolved CO2 and CH4 concentrations; we estimated k from floating chamber deployments in conjunction with discrete CO2 and CH4 water concentration measurements. Diffusive CO2 emissions were higher during dry season than during rainy season, whereas there were no consistent seasonal patterns for diffusive CH4 emissions.

The dataset was originally published in DiVA and moved to SND in 2024.

Tio provtagningskampanjer genomfördes i fyra tropiska reservoarer i Brasilien mellan 2015 och 2017. Reservoarerna är belägna i tre olika biomer, och skiljer sig i storlek, ålder, typ av översvämmad jord, trofiskt tillstånd och typ av användning.

Se engelsk beskrivning för mer information.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Supplemental data: Hotspots of diffusive CO₂ and CH₄ emission from tropical reservoirs shift through time
Keywords: ecology; ekologi; climate; klimat; Climate Science; Klimatvetenskap; Environmental Sciences; Miljövetenskap; Ecology; Ekologi